2016
DOI: 10.1021/acs.analchem.6b01682
|View full text |Cite
|
Sign up to set email alerts
|

Three-Enzyme Cascade Bioreactor for Rapid Digestion of Genomic DNA into Single Nucleosides

Abstract: Structure-based DNA modification analysis provides accurate and important information on genomic DNA changes from epigenetic modifications to various DNA lesions. However, genomic DNA strands are often required to be efficiently digested into single nucleosides. It is an arduous task because of the involvement of multiple enzymes with different catalytic acitivities. Here we constructed a three-enzyme cascade capillary monolithic bioreactor that consists of immobilized deoxyribonuclease I (DNase I), snake veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 56 publications
2
29
0
Order By: Relevance
“…Spectrum Plant Total RNA Kit (Sigma Aldrich) was added into the host root sample for RNA extraction. DNase I was also mixed to remove any genomic DNA in the sample during RNA extraction (Yin et al, 2016). Primers (Table S1) of oligo (dTs) with Super-Script III Frist Strand Synthesis SuperMix (Invitrogen) with s added to generate cDNA library (Hoege et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Spectrum Plant Total RNA Kit (Sigma Aldrich) was added into the host root sample for RNA extraction. DNase I was also mixed to remove any genomic DNA in the sample during RNA extraction (Yin et al, 2016). Primers (Table S1) of oligo (dTs) with Super-Script III Frist Strand Synthesis SuperMix (Invitrogen) with s added to generate cDNA library (Hoege et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…One advantage of the flow mode was that the biocatalyst proved to be more stereoselective than in the batch mode by minimizing the non-catalyzed reaction of benzylamine with the starting thioester, and the overall reaction was strongly accelerated. A three-enzyme cascade capillary monolithic bioreactor consisting of an immobilized deoxyribonuclease I, a snake venom phosphodiesterase, and an alkaline phosphatase, was recently reported to efficiently digest genomic DNA into single nucleosides [56]. Finally, a first application of a micro-reactor based platform to study enzymatic polymerization reactions in continuous flow mode was reported by Kundu and colleagues [57]; a versatile microreactor design enabled enzymecatalyzed ring-opening polymerization of ε-caprolactone to polycaprolactone in continuous mode, in organic media, and at elevated temperatures.…”
Section: Hydrolasesmentioning
confidence: 99%
“…Deoxyribonuclease I, snake venom phosphodiesterase and alkaline phosphatase were immobilized in a silica-based capillary monolith for the digestion of genomic DNA. Enzymatic activity was significantly enhanced upon immobilization and the monolith displayed high operational and storage stability [27]. Chip reactors typically display a bankcard or microscope slide footprint.…”
Section: Microreactors Mesoreactors Macroreactorsmentioning
confidence: 99%